ChemInform Abstract: Asymmetric Synthesis of 3, 4‐Annulated Indoles Through an Organocatalytic Cascade Approach. Issue 19 (13th May 2014) - Caruana, Lorenzo; Fochi, Mariafrancesca; Comes Franchini, Mauro; Ranieri, Silvia; Mazzanti, Andrea; Bernardi, Luca
Abstract Indoles (II) and (V) bearing Michael acceptors at the 4‐position are used in enantioselective organocatalytic cascade reactions with enals (III) and (VI).